DIFFICULTIES WITH BREASTFEEDING PREMATURE NEWBORNS AFTER HOSPITAL DISCHARGE: AN INTEGRATIVE REVIEW - Moraes, Adriana Silva (2021)
This article sought to analyze the causes that make it difficult to breastfeed premature newborns after hospital discharge Method: This is an integrative literature review carried out in the electronic databases LILACS, SciELO and BDENF in the month of another 2020. As a result , a total of 97 articles were generated. After removing duplicates and using the inclusion and exclusion criteria, the final sample consisted of 7 articles. Results: The breastfeeding of premature newborns is directly related to positive and negative factors inherent to the premature baby, to the mother, to the environment in which both live and to the possibility of access to health. The biopsychosociocultural aspects influence and hinder the breastfeeding process, but access to maternal and child health, from the prenatal period until after hospital discharge, were considered positive factors. Conclusion: For the success of breastfeeding, changes in health care offered to the binomial are necessary. These changes include the improvement in maternal health education, better preparation and qualification of health professionals, enabling the effectiveness of breastfeeding even during the hospitalization period and continuity after hospital discharge.